Literature Review: Potensi Senyawa Alkaloid Dalam Inhibisi Enzim Asetilkolinerase Melalui Pendekatan In Silico Untuk Terapi Alzheimer - Annisa, Hilma Tri; Amin, Saeful (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Alzheimer’s disease is a major neurodegenerative disorder characterized by progressive cognitive decline, memory loss, and behavioral impairment. A therapeutic approach widely employed is the inhibition of acetylcholinesterase (AChE) to sustain acetylcholine levels in the synaptic cleft. Alkaloids, abundantly found in medicinal plants, have demonstrated promising activity as AChE inhibitors. With advances in computational techniques, in silico methods including molecular docking, molecular dynamics (MD), density functional theory (DFT), and ADMET prediction are increasingly used to evaluate molecular interactions efficiently prior to in vitro or in vivo validation. This study aims to review the potential of alkaloids in inhibiting AChE through in silico approaches for Alzheimer’s therapy. A systematic literature review was conducted using PubMed, ScienceDirect, ResearchGate, and Google Scholar with structured keywords, covering publications from 2015 to 2025. Out of 15 identified studies, 10 were screened, and 5 met eligibility criteria. The findings indicate that key alkaloids such as berberine, palmatine, huperzine A, and biflavanone exhibited binding affinities comparable to or greater than standard ligands, with stable hydrogen bonding and hydrophobic interactions at the catalytic active site (CAS) and peripheral anionic site (PAS) of AChE. Studies by Qi et al. (2022) and Rawat et al. (2024) confirmed these results through in vitro validation, while Guo et al. (2020) and Negru et al. (2025) reported favorable ADMET profiles supporting their pharmacokinetic feasibility. In conclusion, alkaloids represent strong candidates for Alzheimer’s therapy via AChE inhibition, and in silico strategies play a pivotal role in accelerating active compound screening and drug development efficiency.